2018
DOI: 10.3390/ma11060902
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CNT/PDMS Nanocomposites on the Dynamics of Pioneer Bacterial Communities in the Natural Biofilms of Seawater

Abstract: In this study, the antifouling (AF) performance of different carbon nanotubes (CNTs)-modified polydimethylsiloxane (PDMS) nanocomposites (PCs) was examined directly in the natural seawater, and further analyzed using the Multidimensional Scale Analyses (MDS) method. The early-adherent bacterial communities in the natural biofilms adhering to different PC surfaces were investigated using the single-stranded conformation polymorphism (SSCP) technique. The PCs demonstrated differences and reinforced AF properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Results showed that the type of MWCNTs had an impact on the coating’s AF behavior, as well as on pioneer eukaryotic communities [ 55 ]. Conversely, Ji et al demonstrated that most carboxyl- and hydroxyl-modified coatings had weak modulating effects on pioneer biofilm communities [ 81 ], while Sun and Zhang showed that the AF behavior of these modified CNTs varied for different pioneer biofilm bacteria [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that the type of MWCNTs had an impact on the coating’s AF behavior, as well as on pioneer eukaryotic communities [ 55 ]. Conversely, Ji et al demonstrated that most carboxyl- and hydroxyl-modified coatings had weak modulating effects on pioneer biofilm communities [ 81 ], while Sun and Zhang showed that the AF behavior of these modified CNTs varied for different pioneer biofilm bacteria [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Currently, various studies reported the enhancement of antibiofouling characteristics of PDMS by the attachment of MWCNTs. 158,159 A c c e p t e d M a n u s c r i p t With respect to PDMS/CNTs nanocomposites, various reports have been conducted on their thermal, electrical, and mechanical properties, suggesting that CNTs attachment may be beneficial. [160][161][162][163] Another best example of these composites' application is the production of electrically conductive materials for biomedical implants with sensing ability.…”
Section: Application Of Cnts In Urinary Tract Devicesmentioning
confidence: 99%
“…Despite these excellent properties, as with any other silicone material, PDMS is prone to non-specific surface adsorption of proteins and bacteria, which can be a disadvantage in the biomedical field. Recently, different studies have reported the increase of the antifouling properties of PDMS by the incorporation of MWCNTs [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%